Lycidae, Elateridae (Omalisinae), Prostomidae and Pyrochroidae in the Coleoptera collections of “Grigore Antipa” National Museum of Natural History with the first record of Pyrochroa bifoveata in Romania - Melania Stan (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”, 2025)
The paper deals with twelve species of Lycidae, Elateridae (Omalisinae), Prostomidae and Pyrochroidae from Romania. Photographs of male genitalia and abdominal segments of four specimens of Pyrochroa bifoveata Molfini, Mancini & Bologna, 2022 from Constanța, Brașov, Satu Mare counties and Bucharest are given. Distribution maps based on the examined material are presented for the twelve species.